Ответ:
решение смотри на фотографии
[tex]4c {}^{3} - 32 = 4(c {}^{3} - 8) = 4(c -2 )( {c}^{2} + 2c + 4)[/tex]
[tex](5a + 6) {}^{2} - 81 = (5a + 6) {}^{2} - 9 {}^{2} = (5a + 6 - 9)(5a + 6 + 9) = (5a - 3)(5a + 15) = 5(5a - 3)(a + 3)[/tex]
[tex] {x}^{2} - 2xy + {y}^{2} + x - y = (x - y) {}^{2} + ( x- y) = (x - y)(x - y + 1)[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
решение смотри на фотографии
[tex]4c {}^{3} - 32 = 4(c {}^{3} - 8) = 4(c -2 )( {c}^{2} + 2c + 4)[/tex]
[tex](5a + 6) {}^{2} - 81 = (5a + 6) {}^{2} - 9 {}^{2} = (5a + 6 - 9)(5a + 6 + 9) = (5a - 3)(5a + 15) = 5(5a - 3)(a + 3)[/tex]
[tex] {x}^{2} - 2xy + {y}^{2} + x - y = (x - y) {}^{2} + ( x- y) = (x - y)(x - y + 1)[/tex]